2011
DOI: 10.2337/dc11-0723
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Glucose Profiles in Obese and Normal-Weight Pregnant Women on a Controlled Diet

Abstract: OBJECTIVEWe sought to define 24-h glycemia in normal-weight and obese pregnant women using continuous glucose monitoring (CGM) while they consumed a habitual and controlled diet both early and late in pregnancy.RESEARCH DESIGN AND METHODSGlycemia was prospectively measured in early (15.7 ± 2.0 weeks’ gestation) and late (27.7 ± 1.7 weeks’ gestation) pregnancy in normal-weight (n = 22) and obese (n = 16) pregnant women on an ad libitum and controlled diet. Fasting glucose, triglycerides (early pregnancy only), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
140
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(160 citation statements)
references
References 16 publications
15
140
0
1
Order By: Relevance
“…Maternal obesity is associated with an increase in maternal lipid levels, higher triglycerides and VLDL (21), and lower HDL-C (21) than observed in lean women. Obese women without GDM have been shown to have higher glucose profiles on continuous glucose monitoring performed during pregnancy than normal-weight women; the mean time spent with glucose .6.7 mmol/L is longer in obese than normal-weight women (209 6 62 min vs. 33 6 12 min, P = 0.001) (22). In addition to changes in lipid and glucose metabolism, there is greater inflammation and more vascular endothelial dysfunction associated with obese pregnancy.…”
Section: Maternal Obesitymentioning
confidence: 96%
“…Maternal obesity is associated with an increase in maternal lipid levels, higher triglycerides and VLDL (21), and lower HDL-C (21) than observed in lean women. Obese women without GDM have been shown to have higher glucose profiles on continuous glucose monitoring performed during pregnancy than normal-weight women; the mean time spent with glucose .6.7 mmol/L is longer in obese than normal-weight women (209 6 62 min vs. 33 6 12 min, P = 0.001) (22). In addition to changes in lipid and glucose metabolism, there is greater inflammation and more vascular endothelial dysfunction associated with obese pregnancy.…”
Section: Maternal Obesitymentioning
confidence: 96%
“…Multiple indicators of glucose variability were higher, worse, and correlated more strongly with each other for women with T1D. 22 CGMs have been utilized in special situations in pregnancy, such as pregnancy after Roux-en-Y gastric bypass, 23 obese pregnancies, 24 masked (asymptomatic) hypoglycemia in insulin-treated GDM, 25 and exercise with T1D. 26 Three of the abovementioned studies showed more or similar rates of hypoglycemia among pregnancies with NGT compared with other groups.…”
Section: Cgm Pattern Recognition In Pregnancymentioning
confidence: 99%
“…As discussed earlier, this state of nutrient excess may be associated with a greater longterm risk for adult disease (50) . Maternal obesity and increased plasma lipid concentrations are related to fetal obesity, highlighting the importance of lipid status and potentially of placental fatty acid transfer (28,51,52) . While the maternal-to-fetal transfer of fatty acids, especially of PUFA, has been studied in normal pregnancies (53) , little is known whether and how this may be changed with maternal overnutrition/obesity or gestational diabetes.…”
Section: Fetal Developmental Plasticity and Appropriate Epigenetic Chmentioning
confidence: 99%
“…Accelerated prenatal fetal growth can result from increased fuel supply to the fetus which occurs when maternal blood glucose and lipid levels are increased due to insulin resistance or gestational diabetes mellitus, both of which are prevalent among obese pregnant women. Indeed, maternal blood glucose and TAG concentrations are directly related to neonatal adiposity in obese women (28) . Better control of blood glucose levels, or reduction of insulin resistance during pregnancy through diet and exercise, offer ways of modifying fetal growth and potentially reducing the child's future risk of obesity (29) .…”
Section: Fuel-mediated In Utero Hypothesismentioning
confidence: 99%